Fatherless sons, devoted mentors: Pastoral engagements with the township youth in South Africa - Mahlangu, Solomon S. (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2025)
Fatherlessness in South African townships presents urgent pastoral and theological challenges, particularly among adolescent boys. The absence of a father figure impact young people’s emotional well-being, moral development, and spiritual identity. This article is situated within the broader context of youth vulnerability, where systemic neglect and community-level trauma deepened relational breakdowns. The concern for healing, belonging, and identity among these youth gave rise to the investigation. The article aims to explore how churches might respond pastorally to the crisis of fatherlessness among township youth through theological reflection and ministry practice. It seeks to examine how biblical images of divine fatherhood and the principle of spiritual adoption can inform church-based responses to the emotional and spiritual needs of young men in South Africa’s urban townships. A qualitative theological approach was adopted, relying on the critical review of existing literature, public church material, and reflective analysis of two observed church-based ministries: HOPE to You Community Church and Ebenezer Evangelical Church. The study makes use of theological texts (e.g. Ps 68:5; Jn 14:18; Ja 1:27), pastoral care theory, and observations of practices related to mentorship, narrative care, and community engagement. No formal empirical data were collected. The study finds that relational and spiritual mentorship models grounded in the theology of adoption offered constructive responses to youth disconnection and identity loss. Churches that fostered intergenerational relationships, narrative pastoral practices, and stable mentoring structures were observed to create meaningful spaces of belonging and emotional recovery. Initiatives like the Fathers Matter campaign served as illustrative anchors within these faith communities. The research concludes that local churches, when grounded in contextual theology and committed to relational presence, could play a transformative role in addressing the wounds of fatherlessness. While structural barriers remained, the credibility of the church as a relational institution opened avenues for identity restoration and social resilience among youth. Contribution: This article contributes to the field of contextual pastoral theology by offering theological and observational insights into church-based responses to fatherlessness in township contexts. It proposes biblically rooted and pastorally sensitive models of care that foster emotional healing, nurture a sense of belonging, and support the development of spiritual identity among vulnerable township youth.